2012
DOI: 10.5923/j.library.20120101.01
|View full text |Cite
|
Sign up to set email alerts
|

Use of E-resources by the Students and Researchers of Faculty of Arts, Annamalai University

Abstract: The study aimed at finding the use of e-resources by the post graduate students and research scholars of Faculty of Arts in the Annamalai University. A questionnaire was distributed among the Research scholars and Post-Graduate Students to collect desired data. A total of 200 questionnaires were distributed to the selected sample of Faculty of Arts; 180 valid samples were collected. The study found that the majority of users are aware about the availability of e-resources. The result reveals that 47.78 % of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…The findings above are in consonance with the work of Tella, Ayeni & Omoba (2007) who affirmed that electronic information resources promote scholarship. Similarly, the findings are also in line with the work of Thanuskodi (2012), who reported that students use EIR for various purposes which include writing papers, research and updating knowledge amongst others.…”
Section: Research Question 1: What Are the Types Of Electronic Informsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings above are in consonance with the work of Tella, Ayeni & Omoba (2007) who affirmed that electronic information resources promote scholarship. Similarly, the findings are also in line with the work of Thanuskodi (2012), who reported that students use EIR for various purposes which include writing papers, research and updating knowledge amongst others.…”
Section: Research Question 1: What Are the Types Of Electronic Informsupporting
confidence: 89%
“…Achonna (2008) carried out a study on awareness, access and usage of E-journal by the students of College of Technology, Yaba, Nigeria and found that the use of e-journal resources was low among the students. In a related study on use of electronic information resources among the students and researchers of Faculty of Arts by Thanuskodi (2012), it was revealed that majority of the respondents used electronic resources for various purposes such as writing papers, studying, research purpose, updating knowledge and for examination. In a separate study in Ghana, Akuffo (2019) and Ankrah & Acheampong (2017) revealed that students use electronic resources for research and assignments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…He discovered that although awareness and use of e-journals were high, accessibility was poor due to slow network and regular power cuts. Other studies, such as Dhanavandan and Esmail (2012) and Thanuskodi (2012), also reported high levels of awareness of e-resources. Kumar and Kumar (2010) investigated the perception and use of Indian academics of e-resources and found that the majority of participants used them in their academic work and that many of the students and faculty had learned about e-resources by trial and error or through the advice of friends.…”
Section: Awareness Of E-resourcesmentioning
confidence: 75%
“…Similarly, Egberongbe’s (2011) study showed that the lecturers and research scholars at the University of Lagos made good use of e-resources, to the point of being dependent on e-resources to obtain the relevant information sought. Furthermore, Friedlander (2002), Tenopir (2003) and Thanuskodi (2012) reported that the majority of students and researchers in their studies preferred to use electronic information resources.…”
Section: Literature Reviewmentioning
confidence: 99%